PEMANFAATAN ECENG GONDOK (EICHORNIA CRASSIPES) SEBAGAI PAKAN IKAN NILA (OREOCHROMIS NILOTICUS) DENGAN BAHAN FERMENTASI YANG BERBEDA: The Use Of Water Hyacinth (Eichornia crassipes) As Feed For Tilapia (Oreochromis niloticus) With Different Fermentation Inggredients - Hernayanti, Leni; Sumahiradewi, Luh Gede; Liliyanti, Mita Ayu; Tarmizi, Azhari (Al-Qalbu: Jurnal Pendidikan, Sosial dan Sains, 2024)
This study aims to determine the effect of water hyacinyh fermented with different raw materials: Trichoderma sp., Rhizopus sp., Lactobacillus sp., on the growth of tilapia seeds. This study was designed Completely Randomized Design (CRD) consisting of 3 treatments and 3 replications, namely: P1 (Control), P2 (Tretment of water hyachinth fermented with Trichoderma sp.), P3 (Tretment of water hyachinth fermented with Rhizopus sp.), P4 (Tretment of water hyachinth fermented with Lactobacillus sp.). Tilapia seeds have a weight range of 1.35-2.58 grams and a length range of 4.57-5.16 cm which is stocked in a 47-liter aquarium with a stocking density of 15 birds per experiment container. The test fish was fed as much as 5% of the biomass weight with the frequency of administration three times a day, namely 08:00, 02:00 and 17:00 WIB. The results showed the treatment gave different results on growth in absolute wieight, growth in daily weight, growth in absolute length, growth in daily length, feed conversion ratio, and survival rate. The best treatment occurred at P3 with their respective weight values of 2.659 grams, 0.089 grams, 1.685 cm, 0.056 cm, 2.385%, and 84.444%.